PERAN KOPERASI DALAM MEWUJUDKAN PEMBANGUNAN EKONOMI KERAKYATAN - Turmono (Jurnal Teknologi dan Bisnis, 2022)
Cooperative as a manifestation of the economic development of democracy. This happens when the cooperative is well managed, The existence of cooperatives in the District of Gunungjati has not described the cooperative as a form of economic development populist.This study aims to answer from the questions that become the formulation of the problem, how SWOT Cooperative as a Form of Community Economic Development in the District of Gunungjati? This research uses qualitative research,The data collected by interview technique (interview), observation, documentation and then analyzed by descriptive method of analysis.The SWOT analysis results that can be submitted by the authors are the cooperatives in the District of Gunungjati has the power in management,And has a weakness of the level of public confidence,Besides the cooperative opportunities for cooperation with financial institutions are very open,On the other hand the threat is the ease of provision of borrowers of informants (middlemen) who are still very difficult to overcome.